Horner syndrome due to first rib fracture after major thoracic trauma - art. no. E17 - Ozel, SK; Kazez, A (W B Saunders Co-Elsevier Inc, 2005)
A case of Horner syndrome diagnosed during the follow-up after major thoracic trauma is presented in this report. A 10-year-old boy was admitted to the emergency service with severe thoracic trauma with left clavicular and first rib fracture after a traffic accident. During the follow-tip, myosis and ptosis were recognized in his left eye. Cranial tomography and neurological examination were all normal. The symptoms were thought to be caused by compression of the local hematoma to the cervical ganglia. After 30 days of conservative treatment with tube thoracostomies, he was discharged with his Horner syndrome. After 6 months of follow-up, the findings of Horner syndrome were found to be partially resolved. First rib fracture associated with Horner syndrome is very rarely seen in children, and only 2 cases were found in English-language literature. Our case seems to be the third reported case. Horner syndrome should be kept in mind in cases of first rib fractures. When head trauma is considered, as it can be mistaken with anisocoria, this knowledge may help the surgeon in differential diagnosis. (c) 2005 Elsevier Inc. All rights reserved.
21st Annual Meeting of the Turkish-Association-of-Pediatric-Surgeons -- OCT 08-10, 2003 -- Sanliurfa, TURKEY
Keywords: first rib fracture; pediatric; Horner syndrome; thoracic trauma